ANALISIS KUALITAS PELAYANAN DISTRIBUTION CHANNEL PADA UMKM TAHU BAXO IBU PUDJI DI KABUPATEN SEMARANG - Amindari, Ina; Pradhanawati, Ari (Jurnal Ilmu Administrasi Bisnis, 2019)
The Indonesian economy is currently experiencing an increase, one of the contributors to this success is the MSMEs. One of the SMEs in Semarang Regency is Tahu Baxo Ibu Pudji. Tahu Baxo Ibu Pudji in 2014-2018 has not been able to meet sales targets. Besides several outlets that need to be closed because they are unable to compete in terms of service. Quality of service is a factor that influences purchasing decisions to use services. This research discusses how to improve the quality of distribution channel services, namely by applying 5 dimensions of service quality (physical evidence, reliability, responsiveness, assurance and empathy). The framework for this research is Parasuraman's theory of service quality dimensions. These dimensions will be an analytical tool in answering research questions. The research method used is to use qualitative and by using data collection techniques in the form of observation and interviews. Interviews were conducted with 3 translated sources, namely central employees, outlet employees and consumers. The results of this study indicate the quality of service in the Tahu Baxo Ibu Pudji distribution channel has fulfilled physical dimensions, reliability, responsiveness, assurance and empathy. However, when there are obstacles that become lacking in the physical dimensions, reliability, responsiveness, and empathy. Suggestions given to MSMEs are improvements to the physical dimensions, reliability, responsiveness, and empathy so that they can improve from consumers